BCG-booster vaccination with HSP90-ESAT-6-HspX-RipA multivalent subunit vaccine confers durable protection against hypervirulent Mtb in mice - Kee Woong Kwon; Han-Gyu Choi; Kwang Sung Kim; Shin Ae Park; Hwa-Jung Kim; Sung Jae Shin (npj Vaccines, 2024)
Abstract The quest for effective and enhanced multiantigenic tuberculosis (TB) subunit vaccine necessitates the induction of a protective pathogen-specific immune response while circumventing detrimental inflammation within the lung milieu. In line with this goal, we engineered a modified iteration of the quadrivalent vaccine, namely HSP90-ESAT-6-HspX-RipA (HEHR), which was coupled with the TLR4 adjuvant, CIA09A. The ensuing formulation was subjected to comprehensive assessment to gauge its protective efficacy against the hypervirulent Mycobacterium tuberculosis (Mtb) Haarlem clinical strain M2, following a BCG-prime boost regimen. Regardless of vaccination route, both intramuscular and subcutaneous administration with the HEHR vaccine exhibited remarkable protective efficacy in significantly reducing the Mtb bacterial burden and pulmonary inflammation. This underscores its notably superior protective potential compared to the BCG vaccine alone or a former prototype, the HSP90-E6 subunit vaccine. In addition, this superior protective efficacy was confirmed when testing a tag-free version of the HEHR vaccine. Furthermore, the protective immune determinant, represented by durable antigen-specific CD4+IFN-γ+IL-17A+ T-cells expressing a CXCR3+KLRG1- cell surface phenotype in the lung, was robustly induced in HEHR-boosted mice at 12 weeks post-challenge. Collectively, our data suggest that the BCG-prime HEHR boost vaccine regimen conferred improved and long-term protection against hypervirulent Mtb strain with robust antigen-specific Th1/Th17 responses.